Adult Learning of Novel Words in a Non-native Language: Consonants, Vowels, and Tones - Poltrock, Silvana; Chen, Hui; Kwok, Celia; Cheung, Hintat; Nazzi, Thierry (Frontiers in Psychology, 2018)
While words are distinguished primarily by consonants and vowels in many languages, tones are also used in the majority of the world’s languages to cue lexical contrasts. However, studies on novel word learning have largely concentrated on consonants and vowels. To shed more light on the use of tonal information in novel word learning and its relationship with the development of phonological categories, the present study explored how adults’ ability to learn minimal pair pseudowords in a tone language is modulated by their native phonological knowledge. Twenty-four adult speakers of three languages were tested: Cantonese, Mandarin, and French. Eye-tracking was used to record eye movements of these learners, while they were watching animated cartoons in Cantonese. On each trial, adults had to learn two new label-object associations, while the labels differed minimally by a consonant, a vowel, or a tone. Learning would therefore attest to participants’ ability to use phonological information to distinguish the paired words. Results first revealed that adult learners in each language group performed better than chance in all conditions. Moreover, compared to native Cantonese adults, both Mandarin- and French-speaking adults performed worse on all three contrasts. In addition, French adults were worse on tones when compared to Mandarin adults. Lastly, no advantage for consonantal information in native lexical processing was found for Cantonese-speaking adults as predicted by the “division of labor” proposal, thus confirming crosslinguistic differences in consonant/vowel weight between speakers of tonal versus non-tonal languages. These findings establish rapid novel word learning in a non-native language (long-term learning will have to be further assessed), modulated by native phonological knowledge. The implications of the findings of this adult study for further infant word learning studies are discussed.